أحكام القانون الجنائي في مواجهة الإشهار التضليلي - عبد الله, حساين (University of Eloued جامعة الوادي, 2020)
للإشهار دور كبير في الحياة الاقتصادية، فهو أداة شديدة الأهمية بالنسبة للأطراف المتدخلة فيه. فالمعلن يستخدمه في الترويج لما يقدمه من منتجات أو خدمات و إبراز تفوقها على المنتجات و الخدمات المنافسة، كما يمثل الإشهار مصدرا لإعلام المستهلكين بمختلف خصائص و مميزات المنتجات و الخدمات المعلن عنها. فهو يعتبر حلقة وصل بين المعلن و المستهلك. إلا أن للإشهار آثار سلبية، و ذلك إذا ما استعمله المعلنون بطريقة تضر بمصالح المستهلكين باستخدام طرق احتيالية تتمثل في تضليلهم و تؤدي إلى خداعهم. هذا ما اعتبرته القوانين و الأنظمة بأنه جريمة وجب مواجهتها من خلال توقيع جزاءات جنائية على كل من يرتكبها. Advertising has a big role in the economic life, it is a very important tool for the parties involved in it. Advertiser uses it to promote goods or services he provide and to highlight their superiority over competing goods and services. Moreover advertising is a source of information to consumers about different characteristics and features of the advertised goods and services. It is considered as a link between the advertiser and the consumer. However, advertising has negative effects, when advertisers use it in a way that harms consumers’ interests by using fraudulent methods that mislead and deceive them. This is what laws and regulations considered as a crime that must be deterred and impose criminal sanctions on anyone who commits them.
مجلد11، عدد2
Keywords: الإشهار ; الإشهار التضليلي ; المعلن ; المستهلك ; الجريمة ; العقوبة ; القانون الجنائي; Adevrtising ; misleading advertising ; advertiser ; consumer ; crime ; Sanction ; criminal law